Development of Tourism Village Based on Community Empowerment of Sarwadadi Village Cirebon Regency - Didiet Widiowati; Theresia Martina Marwanti; Enung Huripah (Politeknik Kesejahteraan Sosial Bandung, 2023)
Tourism Villages, which are developed with an approach to economic growth and equity for the welfare of the people, will be able to contribute to increasing the involvement of all elements of society, preserving local resources and wisdom and increasing people's abilities and income. Community empowerment has 3 important aspects, namely social justice, sustainability and equity. The development of tourist villages through community empowerment activities can help accelerate poverty reduction and improve community welfare. The community empowerment process in planning the tourism village development program has three important things, including social mapping, needs assessment, and social analysis. The research method used is qualitative. The type of research used by the researcher is Participatory Action Research. Stakeholder Research Data Sources, Community Leaders, Organizational Leaders. Data collection techniques used in-depth interviews, observations, document studies, and focus group discussions. The research process is Observation (Look), Reflection, Planning (Think) and Implementation (Act). The results showed that (1) all elements of the community were involved and had the same agreement and commitment in all tourism village development processes. (2) Tourism Villages are developed by taking into account aspects of sustainability and environmental sustainability by optimally utilizing existing potential and resources and taking into account local wisdom. (3) The development of tourist villages helps to increase the knowledge, skills and abilities of the community so that they can improve and increase their income and living conditions.